2000
DOI: 10.1128/mcb.20.16.5840-5846.2000
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase-Deficient Mice Develop Nephrogenic Diabetes Insipidus

Abstract: Aldose reductase (ALR2) is thought to be involved in the pathogenesis of various diseases associated with diabetes mellitus, such as cataract, retinopathy, neuropathy, and nephropathy. However, its physiological functions are not well understood. We developed mice deficient in this enzyme and found that they had no apparent developmental or reproductive abnormality except that they drank and urinated significantly more than their wild-type littermates. These ALR2-deficient mice exhibited a partially defective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 30 publications
4
86
0
Order By: Relevance
“…However, under the present experimental conditions, the SORD inhibitor, CP-470,711, did not show any significant effects on the induction of hyperactivated motility. Although our results suggest that aldose reductase is involved in capacitation not by supplying energy sources but by producing low levels of ROS, both enzymes in the polyol pathway might not be indispensable for sperm to fertilize oocytes, because it has been reported that neither aldose reductase-nor SORD-deficient mice demonstrate any apparent reproductive abnormality (Holmes et al 1982, Ho et al 2000. These results suggest that other pathways compensate the deletion of aldose reductase by regulating physiological ROS levels of sperm in mice.…”
Section: Role Of Aldose Reductase In Sperm Capacitationmentioning
confidence: 48%
“…However, under the present experimental conditions, the SORD inhibitor, CP-470,711, did not show any significant effects on the induction of hyperactivated motility. Although our results suggest that aldose reductase is involved in capacitation not by supplying energy sources but by producing low levels of ROS, both enzymes in the polyol pathway might not be indispensable for sperm to fertilize oocytes, because it has been reported that neither aldose reductase-nor SORD-deficient mice demonstrate any apparent reproductive abnormality (Holmes et al 1982, Ho et al 2000. These results suggest that other pathways compensate the deletion of aldose reductase by regulating physiological ROS levels of sperm in mice.…”
Section: Role Of Aldose Reductase In Sperm Capacitationmentioning
confidence: 48%
“…Age-matched nontransgenic littermates were used as controls in all experiments. Aldose reductase knockout (AR À/À ) mice generated in our laboratory (Ho et al, 2000) were back-crossed to the C57BL/6N strain to the 11th generation (N11), which are considered to be congenic with C57BL/6N mice. Age-matched normal C57BL/6N mice were therefore used as control wild-type mice (AR + / + ).…”
Section: Animalsmentioning
confidence: 99%
“…To elucidate the role of the polyol pathway enzymes, AR and SD, in cerebral ischemia and related oxidative stress, we challenged AR-and SD-mutant mice (Ho et al, 2000;Ng et al, 1998) with ischemia/reperfusion injury. The findings that various agents can decrease cerebral infarct size after 2 h of middle cerebral artery occlusion (MCAO) with 22-h reperfusion (Ellsworth et al, 2003;Endres et al, 1998a) suggest that such ischemia-induced brain injury can still be reversed.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme has also been shown to be an obligatory mediator of ischemic preconditioning (Shinmura et al, 2002). Genetic deletion of Akr1b3 in mice leads to the development of nephrogenic diabetes insipidus (Ho et al, 2000), indicating a potentially critical role of the enzyme in concentrating urine.…”
Section: Akr1b1 -Aldose Reductasementioning
confidence: 99%
“…This explains why to-date only four knockout models of the AKRs have been described. Aldose reductase knockout mouse exhibits diabetes insipidus (Ho et al, 2000), whereas Kvβ1 knockout mice have learning and memory impairments (Giese et al, 1998;Need et al, 2003) and alterations in cardiac currents I(to) and I(K slow ) (Aimond et al, 2005). The Kvβ2 knockout has reduced life span, seizures, and exaggerated cold swim induced tremors (Connor et al, 2005;McCormack et al, 2002).…”
Section: B) Homology Between Human and Rodent Akr Genesmentioning
confidence: 99%